(2)=(2)(b+(1))

Simple and best practice solution for (2)=(2)(b+(1)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2)=(2)(b+(1)) equation:


Simplifying
(2) = (2)(b + (1))
2 = (2)(b + (1))
2 = 2(b + 1)

Reorder the terms:
2 = 2(1 + b)
2 = (1 * 2 + b * 2)
2 = (2 + 2b)

Add '-2' to each side of the equation.
2 + -2 = 2 + -2 + 2b

Combine like terms: 2 + -2 = 0
0 = 2 + -2 + 2b

Combine like terms: 2 + -2 = 0
0 = 0 + 2b
0 = 2b

Solving
0 = 2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-2b' to each side of the equation.
0 + -2b = 2b + -2b
Remove the zero:
-2b = 2b + -2b

Combine like terms: 2b + -2b = 0
-2b = 0

Divide each side by '-2'.
b = 0

Simplifying
b = 0

See similar equations:

| (2x+24)+(4x-36)+6x=180 | | 13f=9 | | (2)=(2)(bt(1)) | | 2x+24+4x-36+6x=180 | | 15x-15=113+x | | p=4x+15 | | J-17=(3) | | 3x-10=62 | | 3x-12=15x+24 | | K+20=0 | | 2(g+7)=20 | | 34=0.4(p+22) | | 5n+12+3n=2n+30 | | 12/2=x/15 | | D-3=(2) | | r^3+3r=5 | | 3x-12=15x+8 | | 7x+1.5x=32560 | | 27(n-1)=3(6) | | 3r+13r=-16 | | (x-8)2+(y+2)2=49 | | 27n-1=18 | | 2m-3n=2 | | M-4=(4) | | 4340+4125(215)=891215 | | 5k-14k+(10)=17 | | 4125+(215)=886,875 | | y^2+11y+118=0 | | 5+(10-1)(3)= | | 12b-11b=10 | | 4125(215)=886,875 | | 5a+2b=5 |

Equations solver categories